Enhanced flexibility and thermal conductivity of HfC decorated carbon nanofiber mats. (5th March 2023) - Nisar, Ambreen; Lou, Lihua; Boesl, Benjamin; Agarwal, Arvind
Abstract: Future-generation spacecraft components allude discovery of novel materials that can withstand extreme environments (>2000 °C). The combined effect of ultra-high temperature ceramics (UHTCs) and carbon fibers (Cf ) can satisfy the demanding requirements of aerospace applications. A novel, hybrid, and flexible hafnium carbide (HfC)-decorated carbon nanofiber (C nf ) mat was fabricated via electrospinning. Enhanced thermal stability of the flexible HfC decorated Cnf over Cnf can be elucidated from the 20-fold increment in thermal conductivity and the onset of degradation at higher temperatures (840 °C). Successful integration of multi-layered sandwich lattice using in-housed fabricated HfC decorated Cnf showed retention of the fibrous structure even after extreme spark plasma sintering (SPS) process at 1850 °C. Fabricating a similar multi-layered structure using procured Cf was unsuccessful due to bundled agglomeration and micron-sized fibers. High-load indentation suggests that HfC decorated Cnf interlayer is stronger (∼2.3 times) than the parent UHTC with no cracking at the interface. Compared with the HfC matrix, the indentation-damaged area at the interface reduced up to ∼56% due to toughening mechanisms such as Cnf, fiber pull-out and bridging. The synthesized HfC decorated Cnf mat is proposed as an ultra-thin filler material for joining similar or dissimilar UHTCs while maintaining similar chemistry and better mechanical integrity at the interface. The findings insinuate a new paradigm in designing hybrid and flexible ceramic-containing materials for thermal protection systems (TPS) of future-generation spacecraft components that can mitigate failure in extreme environments (>2000 °C). Graphical abstract: Image 1